2017
DOI: 10.1037/amp0000208
|View full text |Cite
|
Sign up to set email alerts
|

125 years of the American Psychological Association.

Abstract: The American Psychological Association (APA) began 125 years ago as a small club of a few dozen members in the parlor of its founder, G. Stanley Hall. In the decades since, it has faced many difficulties and even a few existential crises. Originally a scientific society, it spent the decades between the world wars figuring out how to accommodate the growing community of applied psychologists while still retaining and enhancing its scientific reputation. After World War II, with an expanded mandate, it develope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 71 publications
0
9
0
Order By: Relevance
“…Psychologists have long understood and worked with the embankment protecting the experimentalists from being tainted by the correlationalists—the pure researchers from the applied (see Cronbach, 1957, for his classic call to unite these two disciplines; see also, Stout, 1987). In fact, disciplinary tensions between academic and professional members of the APA led to the Task Force on the Structure of the APA in 1985 and the consequential creation of the Association for Psychology Science (West, 2008; also see Green & Cautin, 2017, for an overview of APA's long history). Research psychologists, largely experimentalists committed to the ostensible truths of their statistical methods, were exasperated with how the APA was transforming more and more into an association for clinicians and other professionals.…”
Section: Discussionmentioning
confidence: 99%
“…Psychologists have long understood and worked with the embankment protecting the experimentalists from being tainted by the correlationalists—the pure researchers from the applied (see Cronbach, 1957, for his classic call to unite these two disciplines; see also, Stout, 1987). In fact, disciplinary tensions between academic and professional members of the APA led to the Task Force on the Structure of the APA in 1985 and the consequential creation of the Association for Psychology Science (West, 2008; also see Green & Cautin, 2017, for an overview of APA's long history). Research psychologists, largely experimentalists committed to the ostensible truths of their statistical methods, were exasperated with how the APA was transforming more and more into an association for clinicians and other professionals.…”
Section: Discussionmentioning
confidence: 99%
“…She concluded that the assessment battery used "accomplished the purpose by classifying 11 subnormal girls by an objective standard in a relatively short space of time" (p. 249). In 1913, there were only a handful of psychology journals and Eleanor's work was published in the journal Psychological Review (Green & Cautin, 2017), making Eleanor's study likely the first of its kind in or out of the correctional psychology arena.…”
Section: The Bedford Reformatorymentioning
confidence: 99%
“…Now, granted that combining comparative and clinical psychology is a hopeful way of looking at how the APA functions, some may argue that the likelihood for members of one branch of the APA to work with another branch is limited at best and impossible at worst (Green & Cautin, 2017). Terms like "turf wars" are often used to describe large and professionally diverse organizations like the APA.…”
Section: Barriers To Combining Comparative and Clinical Psychologymentioning
confidence: 99%